Asian advantage: - Yip, George S. (Addison-Wesley, 1998)
How a rapidly changing Asia offers new opportunities for Western business. Despite the recent financial turmoil in the region, many Asian economies are restructuring and are poised for sustained growth. Asian Advantage is the most comprehensive strategic resource for analyzing business, political, and cultural conditions in each of Asia's fourteen most vibrant economies. From Australia to Japan to Vietnam, Asian Advantage provides a rigorous and practical framework for evaluating each country's potential role in a company's global strategy. With careful planning, multinational companies can greatly increase their fortunes by expanding into new markets, establishing new production sites, entering into wide-reaching alliances, and tapping new sources of intellectual capital. Featuring the recent experiences of six major multinationals-Matsushita, Motorola, Phillips, Procter & Gamble, Toyota, and Unilever-as well as numerous other companies active in the region, the book shows any company how to create a customized global strategy program for Asia.